Penggunaan Pupuk Kandang pada Pertumbuhan Awal Tanaman Stroberi (Fragaria Sp.) di Tanah Gambut - I Made Tomi Anggara; Akhmad Rizali; Rabiatul Wahdah (Agroekotek View, 2020)
Strawberry plant (Fragaria sp. ) is any kind of fruit having high economic value. In organic farming can be used fertilizer was made by feses waste cattle in which the waste has can change expensive chemical fertilizer. The lowlands are the vast expanse of land with the level of altitude as measured from sea level is relatively low, it is between 0 up to 200 masl. One of the ground in the lowlands is peaty soil. Therefore this study using peaty soil who are in the Suka Maju Village. The purpose of this research to find out the influence of manure on the growth of early strawberry crops in lowland and to know the best dosage early growth strawberry cropping in the peaty soils. This study using a randomized complete design single factor that is a factor contains chicken manure with 8 level treatment. The treatment is applied namely P1 (200 g chicken manure), P2 (300 g chicken manure), P3 (400 g chicken manure), P4 (500 g chicken manure), P5 (200 g cow manure), P6 (300 g cow manure), P7 ( 400 g cow manure) and P8 ( 500 g cow manure). The results of studies indicate the use of manure to the growth early strawberries (Fragaria sp.) on the peaty soil effect has significant different to the parameters the number of branches and real bearing on the number of parameters leaves age 14 weeks after planting parameters and dosage of the best in the number of the branch of the age of 14 weeks after planting with treatment P8 = 16,68 as well with the dose 500 g, to the parameters number of leaves age 14 weeks after planting is P8 = 65,00 g treatment and 500 g dose.